The vociferous count - Кунарев, Андрей (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The article considers the artistic idea and devices of Alexander Pushkin’s epigram on Fyodor Tolstoy “the American”, entitled “David the Singer was short...” (1822). Some semantic nuances are explained and clarified.